Congenital Disseminated HSV-1 Infection in Preterm Twins after Primary Gingivostomatitis of the Mother: Case Report and Review of the Literature - Mercolini, F.; Verdi, F.; Eisendle, K.; Messner, H.; Staffler, A. (Zeitschrift für Geburtshilfe und Neonatologie, 2014)
Transplacental transmission of HSV infection is rare, typically associated with Herpes Simplex Virus 2 (HSV-2) and often reported in term infants, whereas only a few cases of preterm infants with Herpes Simplex Virus 1 (HSV-1) infection are found in the literature. We report the case of a transplacental HSV-1 infection in preterm twins born at 27 weeks gestation. At 23 weeks gestation the mother had experienced primary gingivostomatitis and “flu-like” symptoms, which healed without specific treatment. At birth both infants presented disseminated ulcerated skin lesions at the head, trunk and extremities. Soon after birth, the infants required mechanical ventilation and showed multiple organ involvement. On the basis of the mother’s positive HSV-1 serology, treatment was established before the Tzanck test, serological findings and polymerase chain reaction of the skin and blood had confirmed the neonatal infection. In spite of the early diagnosis within hours after birth and immediate treatment, the extensive skin involvement associated with rapidly progressing multiorgan failure resulted in death of both infants within 3 days. Although a primary HSV-1 infection during pregnancy is extremely rare, gingivostomatitis with general symptoms can lead to transplacental infection and should therefore be taken seriously. Prompt recognition and treatment in the mother are paramount and might be life-saving for the infants.
Keywords: Herpes simplex; transplacental transmission; preterm infants; skin lesions